Factors associated with the occurence of hyperbilirubinemia in infants - Yuni Arisandi; Sodikin (UM Purwokerto Press, 2020)
Hyperbilirubinemia is a problem that often occurs in newborns characterized by icterus, yellowish pigmentation of the skin, sclera, and nails. Many factors cause hyperbilirubinemia in infants such as the type of labor, birth weight, gestational age, gender, and asphyxia.This research aimed to discover the factors associated with the occurrence of hyperbilirubinemia in infants.This was a quantitative research with a retrospective cohort design. There were 83 respondents as the research sample taken using a random sampling technique. The research data were analyzed using the chi-square test and multivariate logistic regression. The majority of respondents underwent labor with actions (59 respondents / 71.1%), delivered male babies (51 respondents / 61.4%), delivered babies with normal birth weight (56 respondents / 67.5%), had a full-term pregnancy (54 respondents / 65.1%), and did not experience asphyxia (65 respondents / 78.3%). In addition, most respondents gave birth to babies with hyperbilirubinemia (43 respondents / 51.8%). Chi-square test results indicated a correlation between the type of labor (p = 0.008), birth weight (p = 0.019), gestational age (p = 0.000), and asphyxia (p = 0.013) with the incidence of hyperbilirubinemia. While the variable of gender (p = 0.106) had no correlation. The most influential factor was gestational age (p = 0.027) with an odds ratio of 4.011. In conclusion: The types of labor, birth weight, gestational age, and asphyxia have a correlation with the occurrence of hyperbilirubinemia.